Effects of Neodymium-Doped Yttrium Aluminium Garnet (Nd:YAG) Laser Irradiation on Bone Metabolism During Tooth Movement - Tsuka, Yuji; Fujita, Tadashi; Shirakura, Maya; Kunimatsu, Ryo; Su, Shao-Ching; Fujii, Eri; Tanimoto, Kotaro (Journal of Lasers in Medical Sciences, 2016)
Introduction: The aim of this study is to evaluate the effects of low-level neodymium-doped yttrium aluminium garnet (Nd:YAG) laser irradiation on orthodontic tooth movement and histological examination. Methods: Eleven male Wistar rats (aged 10 weeks) were included. To produce experimental tooth movement in rats, 10 g force was applied to maxillary first molars with nickel titanium closed coil springs. Right molars were irradiated with Nd:YAG laser on days 0, 1, 2, 3, 7, 10, 14, 17, 21 and 24, while un-irradiated left molars were used as control. Distance between mesial side of second molar and distal side of first molar was measured on μCT image during tooth movement and the rats were sacrificed 4 weeks after the initiation of tooth movement. Results: The amount of tooth movement was significantly greater in the irradiation group (0.20 ± 0.06) than in the control group (0.14 ± 0.03) during the first week (P < 0.05). However, no statistically significant difference was found afterwards. There was a tendency of higher tartrate-resistant acid phosphatase (TRAP)-positive nuclei count in the pressure zones of the laser irradiation group, but it was not statistically significant. In immuno-histological examination, expressions of alkaline phosphatase (ALP) and receptor activator of nuclear factor kappa-B ligand (RANKL) were higher at the pressure site of the laser irradiation group than the control group, whereas there was no difference in osteoprotegerin (OPG) expression. Conclusion: The results suggest that low-level Nd:YAG laser may stimulate osteoclast and osteoblast activation and accelerate bone metabolism during tooth movement.